Interactions Between the Gut Microbiome and Acute Pancreatitis - Nadia Miga-Orczykowska; Ilona Sajkiewicz; Paulina Lemieszek; Ilona Jasiuk; Justyna Wótowicz; Martyna Pustelniak; Katarzyna Krukar; Ewa Łukaszewska; Katarzyna Rudnicka; Klaudia Kister (Journal of Education, Health and Sport, 2024)
Introduction and purpose